Stigma toward people with COVID-19 among Bangladeshi older adults - Mistry, Sabuj Kanti; Ali, A. R. M. Mehrab; Yadav, Uday Narayan; Huda, Md. Nazmul; Rahman, Md. Mahmudur; Saha, Manika; Rahman, Md. Ashfikur; Lim, David; Ghimire, Saruna (Frontiers in Public Health, 2022)
The onset of the COVID-19 pandemic and its overwhelming physical and mental health burden can result in stigmatization towards the disease and those affected. This study aimed to measure the prevalence of COVID-19 related stigma and its associated factors among the older people in Bangladesh. This cross-sectional study was conducted with 1045 Bangladeshi older adults aged 60 years and above through telephone interviews in September 2021. The outcome was measured using an eight-point Stigma Scale, adapted to the Bengali language. Level of stigma was indicated by the cumulative score of the 8-items, ranging from 0 to 8, with a higher score indicating a higher level of stigma. On average participants had stigmas on three of the eight items. The most prevalent stigmas were: COVID-19 is a punishment from God (79.3%), previous COVID-19 patients must be isolated (67.3%), and people infected with COVID-19 did not meet hygiene standards (63.9%). Participants who lived in rural areas (β: 0.67, 95% CI: 0.39 to 0.95) and who perceived needing additional care during the pandemic (β: 0.35, 95% CI: 0.09 to 0.60) had a higher average stigma score, while stigma scores were lower among unemployed/retired participants (β: -0.22, 95% CI: -0.45 to 0.00). The study findings suggest implementing interventions to raise awareness through appropriate educational interventions and mass media campaigns.